Adultes en transition: analyse rétrospective - Perron, Jacques; Tremblay, Chantal (Canadian Journal of Counselling and Psychotherapy, 2011)
The analysis of transitions is different when one intends to predict their outcome from their point of onset (prospective research) or to describe their evolution from their ending point (retrospective research). Based on the latter perspective, this article shows how 56 subjects classified into four outcome groups (project deleted, abandoned, failed or completed), account for their transitions. The corpus of qualitative data gathered from semi-structured interviews was analyzed in terms of the characteristics of the transition itself, those of the persons, those of the environment, and of causal attribution factors. Results showed that on these four types of variables the four groups of subjects differed when reporting the transition they had experienced.